INAKTIVASI MIKROBA Staphylococcus aureus DALAM SUSU MENGGUNAKAN MEDAN LISTRIK BERDENYUT TEGANGAN TINGGI - Nurismanto, Rudi; HP, Sudaryati; Rahmita, Ruhi Dian (UPN VETERAN JAWA TIMUR, 2011)
Pulsed electric field processing represents a promising non-thermal technology which involves the application of pulses of high voltage (20-80 kV/cm) for less than one second to fluid foods placed between two electrodes. During the application of certain PEF conditions microbial inactivation occurs by causing a pore formation and destruction of the cell membranes The purposes of the present study were (i) to inactivated of Staphylococcus aureudecreas using pulsed electric field and (ii) physicochemical properties of raw milk. Intensity field strength that used are 30 and 60 kV/cm, with pulses number 10, 20, and 30. The results showed that higher decrease of population of Staphylococcus aureus with intensity 60 kV/cm and pulses number 30 (0,6 log cycle) and PEF methods give unsignificant effect on pH and total acid.Key words : pulsed electric field, population, Staphylococcus aureus